In-vitro permeability of poorly water soluble drugs in the phospholipid vesicle-based permeation assay: the influence of nonionic surfactants - Fischer, Sarah Maud; Flaten, Gøril Eide; Hagesæther, Ellen; Fricker, Gert; Brandl, Martin (Journal of pharmacy and pharmacology, 2011)
The aim of this study was to determine the influence of nonionic surfactants on drug permeability using the phospholipid vesicle-based permeation assay (PVPA), which excludes other than trans-membrane diffusion pathways.Barrier integrity was monitored both by electrical resistance and permeability measurement of the hydrophilic marker calcein. Permeability of the model drugs ketoprofen and nadolol across the PVPA-barrier was measured by HPLC-UV. Micelle association of the model drugs was determined using ultrafiltration, whereby micelle-bound drug and molecular drug were separated.The nonionic surfactant poloxamer 188 was demonstrated not to affect barrier integrity. Drug permeability was found depressed in the presence of poloxamer 188 in a concentration-dependent manner. Both drugs were found to associate with poloxamer 188 micelles. The extent of the decrease in permeability correlated mostly, but not in all cases, with the fraction of micelle-bound drug.Micelle association was one important but not the only factor affecting drug permeability across the PVPA-barrier.
Gesehen am 16.01.2023